FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR PRODUK TURUNAN KELAPA INDONESIA DI PASAR INTERNASIONA - Muslim, Toufan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is one of the world's largest coconut producers, but the addedvalue of exports of its derivative products remains relatively low. This study aims to empirically examine the significance of Revealed Comparative Advantage (RCA), exchange rates, and selling prices on Indonesian coconut derivative product exports in the international market during the 1990-2023 period. This study employed the Multiple Linear Regression method using Eviews 10 as the analytical tool. The data used were obtained from secondary data from Faostat.Using the aforementioned analytical tools, the results show that RevealedComparative Advantage (RCA) positively influences Indonesian coconut derivative product exports in the international market. Export demand positively influences Indonesian coconut derivative product exports in the international market. The exchange rate positively influences Indonesian coconut derivative product exports in the international market. The variables Revealed Comparative Advantage (RCA), exchange rates, and selling prices simultaneously influence Indonesian coconut derivative product exports in the international market. The government is expected to implement various policies related to Indonesian coconut exports, including product diversification, export subsidies in the form of tax breaks, ease of export processing, and increased market access through promotions and trade missions